Anthropometric profile and dietary intake of amateurs and professional mixed martial arts athletes - João Carlos Alves Bueno; Marcelo Saldanha Aoki; Victor Silveira Coswig; Eduardo Poloni Silveira; Ragami Chaves Alves; Alexandro Andrade; Tácito Pessoa de Souza Junior (Universidad de León, 2024)
Nutritional habits and anthropometric profiles are directly linked to competitive performance; however, there is a great lack of information on amateur or professional mixed martial arts (MMA) athletes outside the competitive period. The aim of this study was to compare food consumption and anthropometric profile of amateur and professional MMA fighters. The sample was composed of 24 male MMA athletes, middleweight category (age: 27.5 ± 5.0 years; body mass: 79.0 ± 12.1 kg; height: 173.5 ± 0.1 cm; %BF: 19.5 ± 4.0 %, BMI: 26.0 ± 2.8 kg/m2). Food consumption was evaluated based on three 24-hour food diaries using the Multi-Step method in a non-competitive period and analyzed using the Dietbox v2.92 software. The professional group was younger (p = 0.001) than the amateur group. Total energy expenditure was similar between amateur (4364 ± 469 kcal) and professional (4312 ± 381 kcal). Amateur and professional reported an energy deficit between the estimated energy requirement and energy intake. Carbohydrate consumption was below the suggested minimum limits (amateur: 3.3 ± 1.6g/kg/day and professional: 3.3 ± 1.4g/kg/day). Protein intake was within the suggested limits (amateur: 1.4 ± 0.9g/kg/day and professional: 1.8 ± 0.8g/kg/day) and lipids presented borderline values about to with concerning the recommendations in the literature (amateur: 0.9 ± 0.6 / g/kg/day and professional: 1.8 ± 0.9 g/kg/day). Amateur and professional athletes did not differ in terms of food consumption and anthropometric profile. Both groups, amateur and professional, demonstrated negative energy balance and inability to reach the suggested levels of macronutrient intake according to the classification. Thus, it is recommended that both MMA groups receive attention regarding nutritional strategies.